Pengaruh Dukungan Suami terhadap Kecemasan Ibu Hamil TM III di Puskesmas Beutong Nagan Raya 2024 - Lailawati Lailawati; Basaria Manurung (Detector: Jurnal Inovasi Riset Ilmu Kesehatan, 2025)
Family support, especially the husband when the mother gives birth, is very much needed, such as the presence of the family and husband to accompany the wife before giving birth or the husband touching the wife's hand with feeling so that the wife will feel calmer in facing the labor process. This study aims to determine the Effect of Husband's Support on the Level of Anxiety in Facing Childbirth in Pregnant Women in the TM III in the Work Area of ​​the Beutong Health Center UPTD, Nagan Raya Regency in 2024. This type of research is a study with a Cross-sectional design (sectional cut). In cross-sectional research, the cause or risk and effect variables or cases that occur in the research object are measured or collected simultaneously (at the same time). The population is all pregnant women in the TM III in the Work Area of ​​the Beutong Health Center UPTD, Nagan Raya Regency in 2024 in May-June, as many as 36 pregnant women. The number of samples used was 36 people obtained using the Total sampling technique. The data analysis technique used chi-square analysis. The results obtained in this study were from 36 respondents, there was a relationship between husband and anxiety levels in facing childbirth using the Chi Square statistical test, a P-value of 0.001 (P <0.05) was obtained, so it can be concluded that Ho is rejected, which means there is a relationship between husband's support and anxiety levels in facing childbirth in pregnant women in TM III.